Effect of Castration on Growth, Fattening and Market value of Black-Head Somali Rams - Yacob, Y.; Fletcher, I.; Kebede, G.; Gizaw, Solomon (1993)
About 60 Black Head Somali rams were used in 21-month experiment period (18 months for growth to maturity and 3 months for fattening) to investigate the effect of age at castration on growth to maturity, fattening capability after maturity and market value of fattened mature rams which had been castrated before puberty (at 6 months of age), during puberty (at 18 months of age), and left entire. All castrated and entire animals were maintained together on natural pasture until 24 months of age, and then were offered 500 kg head-1 per day of concentrate supplement for 3 months. At the end of this fattening period half of the animals were slaughtered for carcass evaluation and the remaining half were sold at local markets to find out the market value. Mortality up to 18 months of age was significantly lower (p less than 0.05) in animals castrated at the age of 6 months than in those left entire. Age at castration had no significant effect on body weight or average daily gain before or after fattening. There were no significant effects among the three treatments on any of the carcass measurements and market values of the animal caused by castration or age at castration.